KEBIJAKAN HUKUM PIDANA DALAM UPAYA PENANGGULANGAN TINDAK PIDANA MELALUI PENYELESAIAN DI LUAR PROSES - Jati Kusuma (SOL JUSTICIA, 2019)
The development of criminal law is seen as an act of damaging or harming the interests of others and is followed by retaliation. Retaliation is generally not only an obligation of someone who is harmed or affected by action, but extends to the obligation of all families, families and even some things become obligations of the community. The logical consequence of the developmental dimensions of criminal law as the context above, there is a private nature of criminal law. Over time, on the one hand the changes and dynamics of the community are very complex and the legal community is relatively more advanced, the criminal law then leads, born, grows and develops to become part of public law as it is known today. On the other hand, the regulation on the making of legislation as a partial legislation turns out that the public nature of criminal law is shifting because it also enters the private sphere as it is known and practiced as a form of "non-process settlement", although many normative frameworks are questioned but in reality there is also the practice of settling criminal cases outside the criminal justice system. Gradually, criminal law as part of public law aims to protect the interests of the people and the state by making a balanced and harmonious balance between crime on the one hand from the actions of the authorities acting arbitrarily on the other